The Efficacy of Multidisciplinary Team Co-Management Program for Elderly Patients With Intertrochanteric Fractures: A Retrospective Study - Fan, Jixing; Lv, Yang; Xu, Xiangyu; Zhou, Fang; Zhang, Zhishan; Tian, Yun; Ji, Hongquan; Guo, Yan; Yang, Zhongwei; Hou, Guojin (Frontiers in Surgery, 2022)
Background Intertrochanteric fractures increased quickly in past decades owing to the increasing number of aging population. Recently, the geriatric co-management was rapidly emerging as a favored clinical care model for older patients with hip fractures. The purpose of this study was to assess the efficacy of a multidisciplinary team (MDT) co-management program in elderly patients with intertrochanteric fractures. Methods In this retrospective study, patients were divided into multidisciplinary team (MDT) group and traditional orthopedic care (TOC) group according to the healthcare model applied. 249 patients were included in the TOC group from January 2014 to December 2016 and 241 patients were included in the MDT group from January 2017 to December 2019. Baseline data, peri-operative data and post-operative complications were collected and analyzed using SPSS 21.0 Results No significant differences were observed between two groups in terms of patient baseline characteristics. Patients in the MDT group had significantly lower time from admission to surgery and length of stay (LOS) compared with those in the TOC group. Furthermore, the proportion of patients receiving surgery within 24h (61.4% vs 34.9%, P<0.001) and 48h (80.9% vs 63.5%, P<0.001) after admission to the ward was significantly higher in the MDT group compared with those in the TOC group. In addition, patients in the MDT group had significantly lower proportion of post-operative complications (25.3% vs 44.2%, P<0.001), DVT(7.9% vs 12.9%, P=0.049), pneumonia (3.8% vs 8.0%, P=0.045) and delirium(4.1% vs 9.2%, P=0.025) compared with those in the TOC group. However, no significant changes was found for in-hospital and 30-day mortality. Conclusions The MDT co-management could significantly shorten the time from admission to surgery, LOS and reduce the post-operative complications for elderly patients with intertrochanteric fractures. Further research was needed to evaluate the impact of this model on patient health outcomes.